Fistula care in the digital era: A discussion on the digitization of fistula care in five UNFPA countries - Michaelson, Bryony (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The objective of this project was to partner with five different UNFPA countries in order to collect archived data on the occurrence of obstetric fistula, and to visualize our initial findings on the various contributors to the condition, using data visualization dashboards and mapping tools. One year into its partnership with UNFPA, Operation Fistula takes this opportunity to share the initial findings from the digitization of obstetric fistula data from its five partner countries. Operation Fistula focuses on using technology to facilitate coordination between key stakeholders in the obstetric fistula sector. Methods: The first phase of the project involved data collection via the digitizing of nine unique patient record sheets onto a mobile data collection platform (CommCare) from our five partner countries: Bangladesh, Cameroon, Madagascar, Malawi and Nepal. We have visualized the data we have received thus far in an effort to gain clarity on sociodemographic data, location, surgical and patient outcomes in these five countries. Once their data has been visualized, our partners are able to access and analyze their data with the provision of a Tableau license. Results: We have collected 1,046 patient records across our five partner countries. An initial analysis of these countries has begun to show key trends within the fistula sector, in sociodemographic background, geographic location, and obstetric history. Conclusions: While there have been limitations to our data collection, the preliminary outcomes of the data visualizations, produced have been insightful, and have provided us with a strong basis for further study.